A computational framework for ranking prediction of cloud services under fuzzy environment. Issue 1 (2nd January 2022) - Kumar, Rakesh Ranjan; Shameem, Mohammad; Kumar, Chiranjeev
ABSTRACT: In this work, we propose a framework to assess the many cloud services based on the QoS criteria value in fuzzy environment. Here, we uses the Fuzzy-AHP method to define the architecture of overall cloud service selection process and calculate the weights of QoS criteria. These calculated criteria weight are utilised with TOPSIS method to evaluate the final rank of cloud service based on their overall performance. A comprehensive evaluation illustrates the potential of our proposed methodology, which demonstrates how effective it is when compared to the Cloud service selection decision-making technique